Pathways linking war and displacement to parenting and child adjustment: A qualitative study with Syrian refugees in Lebanon - Sim, A; Fazel, M; Bowes, L; Gardner, F (Elsevier, 2018)
Forcibly displaced children are at risk of a range of negative outcomes, yet little is known about how to support war-affected caregivers in promoting children's psychosocial resilience. The current study uses qualitative methods to examine the mechanisms underlying the effects of war and displacement on parenting and child adjustment in order to inform intervention development. In April and November 2016, group and individual interviews were conducted with 39 Syrian parents and 15 children in partnership with a humanitarian organization in Lebanon. Interviews were transcribed and analyzed using a grounded theory approach. Results show three interrelated pathways linking daily displacement stressors to various dimensions of parenting: (1) economic hardship prevents parents from meeting their children's basic needs and forces adaptation strategies that impair positive parent-child interactions; (2) parental psychological distress contributes to harsh parenting; and (3) perceptions and experiences of insecurity in the community results in increased parental control. Greater economic resources and social support emerged as potential protective factors for maintaining positive parenting despite exposure to war and displacement-related adversity. Our findings suggest that implementation of policies and programs to remove structural barriers to refugees' physical and economic security can have tangible impacts on parental mental health, parenting quality, and child psychosocial outcomes. Future research priorities include a stronger focus on the effects of war and displacement on family processes, taking into account interactions with the broader social, economic and political context.